Effect Of Spoiler Angle On The Aerodynamic Performance Of Hatchback Model - Cheng, See Yuan; Abdullah, Mohd Azman; Mansor, Shuhaimi (Research India Publications, 2017)
Rear spoiler is a device commonly found on road vehicles for improving their aerodynamic performance. The main aim of the present study was to investigate the effect of varying the spoiler angle on the aerodynamic performance of hatchback vehicles. A simplified road vehicle model was used to facilitate the investigation. The study utilized a RANS-based computational fluid dynamics (CFD) method. As for the purpose of validating the method, the numerically obtained results was compared to the experimental data. The numerical result shows that at positive spoiler angle, the aerodynamic lift of the hatchback model has reduced dramatically – up to 2937%. However, the spoiler effect is unfavorable to lift reduction when configured at negative inclination angle. Although the aerodynamic lift was found to decrease with the increase in spoiler angle, there is accompanied by a drag penalty. Finally, the physical mechanism was discussed based on flow visualization results.